Implementation of Management Accounting Information System for Company Policy-Making - Kariyoto Dr (Program Pendidikan Vokasi Universitas Brawijaya, 2014)
Managament accounting information system consists of full cost accounting information, differential accounting information and responsibility accountingl. The aim of this study is to explain the application of management accounting information system on information objects such as products and activities of the department which will result full accounting information. If the system is connected with the alternative that will be selected, it will produce the concept of differential accounting information which is needed for the purpose of management decision making with multiple alternative selection. If the management accounting information system is connected with the authority of the manager, it will produce the concept of responsibility accounting information that is useful to influence company policy-making.